1995
DOI: 10.1901/jeab.1995.64-299
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons' Preference for Variable‐interval Water Reinforcement Under Widely Varied Water Budgets

Abstract: Water budget of pigeons was varied to assess the dependence of risk-sensitive preferences upon economic context such as has been reported for energy-budget manipulations with small animals in behavioral ecology research. Fixed- and variable-interval terminal-link water schedules reinforced choice between equal variable-interval initial-link schedules arranged on two pecking keys. While keeping a severely restrictive budget the same across three phases of the experiment, a contrasting distinct ample budget was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
2
22
1
Order By: Relevance
“…In the earliest demonstration of this effect, Hermstein (1964) asked pigeons to choose between an outcome providing food reward on a fixed-interval (FI) 15-sec schedule in which reward occurred for the first response after 15-sec had elapsed and an outcome providing food on a variable-interval (VI) 15-sec schedule in which reward occurred for the first response after a variable period of time, averaging 15-sec. Herrnstein Such risk-preference with reinforcer-delay risk has been found despite differences in procedures, reinforcement schedules, types of reinforcement and the species under investigation (Aheam et al, 1992;Kacelnik, 1995, 1997;Case et al, 1995;Cicerone, 1976;Davison, 1969Davison, , 1972Frankel and Vom Saal, 1976;Gibbon et al, 1988;Hursh and Fantino, 1973;Kendall, 1987Kendall, , 1989Killeen, 1968;Logan, 1965;Morris, 1986;Navarick and Fantino, 1975;Pubols, 1962;Rider, 1983;Sherman and Thomas, 1968;Zabludoff et al, 1988).…”
Section: Choosing Between Certain and Variable Outcomesmentioning
confidence: 99%
“…In the earliest demonstration of this effect, Hermstein (1964) asked pigeons to choose between an outcome providing food reward on a fixed-interval (FI) 15-sec schedule in which reward occurred for the first response after 15-sec had elapsed and an outcome providing food on a variable-interval (VI) 15-sec schedule in which reward occurred for the first response after a variable period of time, averaging 15-sec. Herrnstein Such risk-preference with reinforcer-delay risk has been found despite differences in procedures, reinforcement schedules, types of reinforcement and the species under investigation (Aheam et al, 1992;Kacelnik, 1995, 1997;Case et al, 1995;Cicerone, 1976;Davison, 1969Davison, , 1972Frankel and Vom Saal, 1976;Gibbon et al, 1988;Hursh and Fantino, 1973;Kendall, 1987Kendall, , 1989Killeen, 1968;Logan, 1965;Morris, 1986;Navarick and Fantino, 1975;Pubols, 1962;Rider, 1983;Sherman and Thomas, 1968;Zabludoff et al, 1988).…”
Section: Choosing Between Certain and Variable Outcomesmentioning
confidence: 99%
“…However, Equation 1 makes no provision for global variables such as economic context or resource availability. Indeed, at least two studies with concurrent chains found no effect of economic context upon choice (LaFiette & Fantino 1989;Case et. al.…”
Section: R E V I E W C O P Ymentioning
confidence: 99%
“…As predicted by the matching law, the aggregate proportional response rates of the pigeon flock on the two response alternatives matched the proportional reinforcement rate associated with those alternatives. Analogous methods were reported by Case, Nichols, and Fantino (1995) to evaluate pigeons' preference for VI reinforcement under varied water budget arrangements. Finally, Hantula and Crowell (1994) showed that the matching law predicted response allocation on a computerized analogue investment task.…”
Section: Timothy R Vollmer and Jason Bourret University Of Floridamentioning
confidence: 99%